"We should have held this in a circle": White ignorance and answerability in outdoor education. Issue 2 (4th March 2023) - Brooks, Spirit Dine'tah; Sabzalian, Leilani; Weiser-Nieto, Roshelle; Springer, Shareen
Abstract: This critical ethnography highlights an ongoing research partnership between two Indigenous studies scholars and their effort to prepare outdoor educators to support Indigenous students more effectively in their programs. After a listening session at the Oregon Indian Education Association annual conference where Indigenous educators and community members urged the Oregon State University Outdoor School 1 program to address how outdoor education reproduced stereotypes of Indigenous peoples and appropriated Indigenous knowledge systems, the authors developed and implemented a series of professional development workshops for outdoor educators in various regions throughout Oregon. The workshops sought to prepare outdoor educators to more effectively support Indigenous students in their classrooms and schools. This article documents the ways outdoor educators embraced or evaded those concepts and commitments and offers recommendations for outdoor education programs and professional development.